Optimization of Degradation Profile for New Scaffold in Cartilage Repair. (October 2018) - Shah, Sarav S.; Liang, Haixiang; Pandit, Sandeep; Parikh, Zalak; Schwartz, John A.; Goldstein, Todd; Lavelle, Lawrence P.; Datta, Arindam; Grande, Daniel A.
Objective: To establish whether a novel biomaterial scaffold with tunable degradation profile will aid in cartilage repair of chondral defects versus microfracture alone in vitro and in a rat model in vivo . Design: In vitro —Short- and long-term degradation scaffolds were seeded with culture expanded articular chondrocytes or bone marrow mesenchymal stem cells. Cell growth and differentiation were evaluated with cell morphological studies and gene expression studies. In vivo —A microfracture rat model was used in this study to evaluate the repair of cartilage and subchondral bone with the contralateral knee serving as the empty control. The treatment groups include (1) empty osteochondral defect, (2) polycaprolactone copolymer–based polyester polyurethane–urea (PSPU-U) caffold short-term degradative profile, and (3) PSPU-U scaffold long-term degradative profile. After placement of the scaffold, the rats were then allowed unrestricted activity as tolerated, and histological analyses were performed at 4, 8, and 16 weeks. The cartilage defect was measured and compared with the contralateral control side. Results: In vitro —Long-term scaffolds showed statistically significant higher levels of aggrecan and type II collagen expression compared with short-term scaffolds. In vivo —Within 16 weeks postimplantation, there was new subchondral bone formation in both scaffolds. Short-term scaffolds had a statistically significant increase in defect filling and better qualitative histologic fill compared to control. Conclusions: The PSPU short-term degradation scaffold may aid in cartilage repair by ultimately incorporating the scaffold into the microfracture procedure.